VD_FINDINFO HC / 2011 / 437 vom 12. August 2011 - VD Tribunal cantonal (2011)
DÉTENTION AUX FINS D'EXPULSION, MESURE DE CONTRAINTEDROIT DES ÉTRANGERS | 76 al. 1 let. b ch. 3 LEtr, 76 al. 1 let. b ch. 4 LEtr